Burnout syndrome in health professionals in times of COVID-19: a systematic review - Tapullima-Mori , Calixto (2021)
COVID-19 spread very quickly worldwide, although the general population has been affected, the groups with the highest level of vulnerability to the virus and its psychological consequences are health personnel. The objective was to evaluate burnout syndrome in health professionals in times of COVID-19 in databases containing scientific literature. We worked under a qualitative approach and analyzed 19 articles from primary sources indexed in Scielo, Redalyc, Scopus, DOAJ, Dialnet and Ebsco. In the first instance, 1586 articles were obtained, of which only 19 met the criteria set. A greater presence of articles with cross-sectional observational descriptive design was observed, the total sample was health professionals, where high burnout rates reached 95% of all the articles analyzed and with a higher prevalence in women than in men, thus concluding that burnout is high in health professionals; In addition, for the presence of burnout, contact with COVID-19 patients, schedules and work overload have been a primary factor for their symptoms to be triggered.